The mediating effect of after-midnight use of digital media devices on the association of internet-related addictive behavior and insomnia in adolescents - Lederer-Hutsteiner, Thomas; Müller, Kai W.; Penker, Matthias; Stolz, Erwin; Greimel, Elfriede R.; Freidl, Wolfgang (Frontiers in Public Health, 2024)
Background There is evidence that overexposure to digital media devices (DMD) can not only lead to addictive patterns of internet use, but also cause insomnia symptoms. The aim of this cross-sectional study among adolescents is to provide an estimate of the prevalence of sleep impairments and to explore the mediating role of after-midnight use of DMD between internet-related addictive behavior (IRAB) and insomnia. Methods 2,712 school students from Styrian schools participated in a population-representative online survey in a supervised school setting in spring 2022. School students were screened using established and validated scales. Data analysis was carried out using multiple imputation, linear multilevel regression and mediation analysis. Results Prevalence estimation indicates high proportions of clinically relevant moderate [12.6% (11.3%; 14.1%)] and severe [3.6% (2.9%; 4.4%)] insomnia, with an additional 30.6% (29.0%; 32.2%) at subthreshold level. DMD are typically used after midnight an average of 1.66 (1.58; 1.75) evenings with subsequent school day per school week. Linear multilevel regression analysis shows significant associations for sleep disparities as outcome variable e.g., with generalized anxiety [b = 0.329 (0.287; 0.371)], after-midnight use of DMD [b = 0.470 (0.369; 0.572)] and IRAB [b = 0.131 (0.097; 0.165)]. Mediation analysis shows a mediated proportion of 18.2% (13.0%; 25.0%) of the association of IRAB and insomnia by after-midnight use of DMD [Indirect effect: b = 0.032 (0.023; 0.040), direct effect: b = 0.127 (0.083; 0.170)]. Conclusions Although the cross-sectional nature of this study limits causal inference, the results indicate a need for policies, which are already in preparation in Styria as part of a respective action plan.